PENGARUH KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN TERHADAP CITRA PERUSAHAAN PT PLN (PERSERO) RAYON BUKITTINGGI - Yolla Ningsih; Anuar Rasyid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
PLN (Persero) is one of the State-Owned Enterprises (BUMN) which is engaged in the supply of electricity, whose existence is greatly needed by the community. The State Electricity Company (PLN) as an important instrument in development, the presence of BUMN in Indonesia is felt very important not only by the government but also by the wider community. So from that PT PLN (Persero) always strives to continually update performance in providing increasingly optimal services, so that the image of PT PLN (Persero) in the eyes of the community will always be considered good and provide good service so as to satisfy the customer.This study uses quantitative research methods, with data collection techniques, namely through questionnaire dissemination to customers of PT PLN (Persero) Bukittinggi raon with a large number of samples of 100 respondents determined using accidental sampling. The analysis technique in this research data uses explanatorystatistics.The results of this study indicate that the influence of service quality and customer satisfaction on the image of the company PT PLN (Persero) Bukittinggi district is positive and significant, because it has a significant value that is smaller than the determined alpha level so that the hypotheses submitted together can be accepted. This is seen from multiple linear regression in this study is equal to Y = 10.197 + 0.429 X1 + 0.510 X2. Meanwhile the constant value of 0.637 means that the contribution of service quality variables and customer satisfaction to the company's image at PT PLN (Persero) Bukittinggi Rayon is 63.7% while the remaining 36.3% is influenced by other variables not included in the research that the author do this.Keyword: Customer Quality, Customer Statisfaction, Company Image.